1997
DOI: 10.1103/physrevb.56.12161
|View full text |Cite
|
Sign up to set email alerts
|

Charge redistribution at Pd surfaces:Ab initiogrounds for tight-binding interatomic potentials

Abstract: A simplified tight-binding description of the electronic structure is often necessary for complex studies of surfaces of transition metal compounds. This requires a self-consistent parametrization of the charge redistribution, which is not obvious for late transition series elements (such as P d, Cu, Au), for which not only d but also s − p electrons have to be taken into account. We show here, with the help of ab initio FP-LMTO approach, that for these elements the electronic charge is unchanged from bulk to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…On the other hand, in several recent experimental studies [76,82,96,[119][120][121][122][123][124][125], a decrease in catalytic activity with particle size below ca. 3 nm has been observed indicating that increasing the surface area of nanoparticulate catalysts may not work in the limit of ultra small particles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, in several recent experimental studies [76,82,96,[119][120][121][122][123][124][125], a decrease in catalytic activity with particle size below ca. 3 nm has been observed indicating that increasing the surface area of nanoparticulate catalysts may not work in the limit of ultra small particles.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of well defined monodisperse size-tunable core-shell nanoparticles [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] have shown that different kinds of size effects proliferate in the nanoworld and influence such different properties as light absorption [112], melting point [113], standard electrode potential [114], photoelectric yield [115,116], surface plasmon frequency [117,118], etc. The size effect in catalysis of methanol oxidation on ultrasmall nanoparticles Pt n (with size: 1-3 nm) has been attributed to the stronger binding of CO ad [76,82,96,[119][120][121][122][123][124][125] due to large surface strain [126] induced by high curvature of small nanoparticles and the resulting contraction of the lattice parameter, which may be as high as 5% [82]. A considerable change in chemisorption and catalytic properties may then likely result [126] from an upward shift in the d-band center, toward the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix elements h i,j,α,β , where i, j and α, β design sites and orbitals respectively, are taken from the fits to the chain and to the bulk ab-initio band structure. As a self-consistency condition we impose local charge neutrality by fixing the charge of the d orbitals and sp orbitals within the chain equal to the ones of the infinite chain [13]. The corresponding condition is also imposed on the electrodes surfaces.…”
mentioning
confidence: 99%
“…The first solution yields [60]. In both cases, the proper treatment of sp-d hybridization thus leads to a dependence of the band term which is intermediate between square-root and pairwise.…”
Section: Second Moment Approximation For Pd-pd Interactionsmentioning
confidence: 94%